Современные аспекты анализа платежеспособности и ликвидности со стороны внешних субъектов финансирования - Мартынов, Г.А.; Харченко, В.А. (Культура народов Причерноморья, 2013)
Определены природа и сущность платежеспособности и ликвидности, обоснована
необходимость проведения анализа платежеспособности на предприятиях, приведена характеристика
основных коэффициентов платежеспособности и ликвидности с указанием нормативных значений,
рассмотрены преимущества и недостатки применения системы показателей платежеспособности на
предприятиях, проведен анализ платежеспособности и ликвидности с точки зрения внешних субъектов
финансировании. Использование этого анализа позволит повысить качество аналитической оценки
финансового состояния предприятия со стороны внешних субъектов финансирования.
Ключевые слова: платежеспособность, ликвидность, анализ, внешние субъекты финансирования. Визначена природа та сутність платоспроможності та ліквідності, обґрунтована
необхідність проведення аналізу платоспроможності на підприємстві, приведена характеристика
основних коефіцієнтів платоспроможності та ліквідності з відображенням нормативних значень,
розглянуті переваги та недоліки застосування системи показників платоспроможності на
підприємстві, проведений аналіз платоспроможності та ліквідності з точки зору зовнішніх суб’єктів
господарювання. Використання цього аналізу дозволить пыдвищити якість аналітичної оцінки
фінансового стану підприємства з боку зовнішніх суб’єктів фінансування.
Ключові слова: платоспроможність, ліквідність, аналіз, зовнішні суб’єкти господарювання. This article is dedicated to today's current questions of analyzing nature and the essence of solvency
and liquidity. The author grounds the necessity of analyzing the solvency of enterprises, and points out the
characteristics of the main ratios of solvency and liquidity by using indicators of values. It also considers the
advantages and disadvantages of using the value system in the enterprises. The currency of the given article is
grounded by the ability of getting credits, investments, and other kinds of loans. Also it’s value for the enterprise
is dependent mainly on applying quite a high level of solvency, where creditors present loans. Special attention
has been devoted to analyzing solvency and liquidity from the point of view of external subjects of financing.
The author states such a approach towards such analysis depending on the source of finding the loans, as well
as the sum and term of the loan. As well as different peculiarities and factors. He also considers the indicators
of such a analysis for making a decision, for receiving additional loans by external subjects of financing. Use of
such analysis will allow to increase the quality of analytical evaluation of financial condition of the enterprise
from the external subjects of financing.
Кeywords: solvency, liquidity, analysis, external subjects of financing.